Response of Chickpea to the Rhizobia Inoculation in Different Region of Morocco - Abdelkader, Machehouri; Btissam, Ben Messaoud; Omar, Zennouhi; Laila, Nassiri; Jamal, Ibijbijen (Canadian Journal of Agriculture and Crops, 2017)
The objective of the present study is to assess the effect of rhizobia inoculations on the growth and nodulation of Chickpea. One rhizobia strains were used as control and soils sampled from eleven sites belonging to six different regions of Morocco. The rhizobia inoculation was applied at the time of the seedling, and the nitrogen fertilizer was performed three times the first application at the seedling moment then two and three weeks after the first application. The biomass and nodulation were evaluated under different treatments. The essay was realized at the greenhouse the Faculty of Sciences, Moulay Ismail University. The Inoculation with these root symbionts, increased the biomass accumulation of the chickpea treated compared to the absolute control. However, the best response result was that of the simple rhizobial inoculation which showed a very good growth as well as an important root infection assisted by the number and weight nodule compared to the rhizobial inoculation combined to the nitrogen fertilization and to the control plants. Finally, the symbiosis with rhizobia is an important biological technology to improve the sustainable production of leguminous plant in different agro-ecological regions.